Consorciação de Capim Aruana com amendoim forrageiro e adubação nitrogenada no desempenho e comportamento ingestivo de novilhos de corte - Biesek, Ronaldo Rubens (2017)
The use of leguminous in consortium can to possibility the decrease in the use of nitrogen fertilizers and increase the nutritive value of the grass. The experiment was carried at the year 2015 and 2016. The experimental area used belongs to the Universidade Tecnológica Federal do Paraná - Câmpus Dois Vizinhos. The experimental area was 6.3 ha, divided into 9 paddocks, with an average area of 0.7 ha, and more one adjacent area to maintain the regulating animals. Aruana grass (Panicum maximum cv. Aruana) and pinto peanut (Arachis pintoi) were implanted in September 2014. The objective of this work was to evaluate the ingestive behavior, patterns of displacement, animal performance, yield and nutritive value of the grass Aruana and marmalade grass (Brachiaria plantaginea) intercropped with pinto peanut or nitrogen fertilized. Two nitrogen doses 100 kg ha-1 and 200 kg ha-1 were used, divided in four applications, the experimental period was 112 days. The treatments were aruana grass + forage peanut + 100 kg ha-1, Aruana grass + 100 kg ha-1, Aruana grass + 200 kg ha-1. The grass was managed using 42 whole animals of 15 months, with mean initial live weight of 330 kg, of these 27 were testers and 15 regulators. The design was completely randomized with three treatments and three replicates. Nitrogen application and intercropping with pinto peanut had no effect (P> 0.05) about the individual performance, ingestive behavior and displacement patterns. The crude protein content of the leaf lamina of the aruana grass were higher (P <0.05) for the consortium and 200 kg N ha-1, however, the leaf mass was higher only for the application of 200 kg N ha- 1 providing highest weight gain per area.